Anomalous Experiences Reported by Nurses: Personality, Perceptual, and Cognitive Factors - Parra, Alejandro (Journal of Scientific Exploration, 2018)
The aim of this study was to determine the degree of occurrence of certain unusual perceptual experiences in hospital settings often related by nurses and carers. Three hundred forty four nurses were recruited from 36 hospitals and health centers in Buenos Aires, who were grouped 235 experiencers and 109 nonexperiencers. The most common experiences are sense of presence and/or apparitions, hearing noises, voices or dialogues, crying or complaining, intuitions and extrasensory experiences and as listerners of experiences of their patients, such as near death experiences, religious interventions, and many anomalous experiences in relation with children. The rationale of the present study is confirm the early findings for work stress and absorption with a bigger sample of nurses (Parra & Gimenez Amarilla, 2017) and additionally, schizotypy proneness and empathy skills. Nurses who report anomalous experiences tended to score higher on work stress was not confirmed, however depersonalization factor scored higher than nonexperiencers. Nurses reporting these experiences tended to report higher scores of absorption and higher scores of proneness to schizotypy, mainly “positive” schizotypy (Unusual experiences) and tended to report higher cognitive empathy and emotional comprehension than non experiencers.